PENDIDIKAN ISLAM DI SAUDI ARABIA - Muhdi Muhdi (ADIBA : JOURNAL OF EDUCATION, 2021)
Islamic education in Saudi Arabia has very strong historical roots, because in this hemisphere the beginning of Islamic education was actually started by the Prophet Muhammad so that it became an inspiration in building systems, curricula, and implementation of education.